A chemical study (Ascorbic acid and essential oil) of Ballota nigra L. (Lamiaceae) . - سلطان عبير (Latakia University Journal -Biological Sciences Series, 2023)
Ballota nigra L. (black horehound) has a medical importance because it contains a wide variety of compounds which used to treat many of diseases. It is known for many countries as a traditional medicine especially for its mild sedative and tranquilizer properties. A chemical study of leaf and flowering aerial parts extract showed presence of ascorbic acid (Vit. C) in leaves more than in flowering aerial parts. The extraction of essential oil from the flowering aerial parts of B.nigra has been done by dry evaporation using GC/MS technique , chromatographic analysis of these extracts have showed the presence of several compounds including terpenes , hydrocarbons , carboxylic acids , esters …. The main compound of the oil was Phytol (41.21%) .